Ante/Para/Post— Theory - Omedi Ochieng (Communication and Race, 2024)
This essay invites thought on the structure, texture, and limits of theory in the North Atlantic university humanities as brought into relief by Israel’s ongoing genocidal campaign against the Palestinian people. I suggest here that the deep idiomatic and affective reflexes of theory are emergent and contoured by the imperial colonial imagination as it undergoes decomposition from ecological collapse, pandemics, global capitalist deterioration, and unyielding insurgent resistance. Creative and critical theory in the university, I ultimately argue, is a tertiary prose of counterinsurgency whose chiasmic codes absorb insurgent energies, scrambling and recoding them in terms set by the political unconscious of racial capitalist catastrophism.